2009
DOI: 10.1111/j.1651-2227.2008.01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent basal insulin patterns in children with type 1 diabetes treated with continuous subcutaneous insulin infusion

Abstract: Basal insulin infusion rate profiles in well-controlled paediatric patients on CSII reflect the age-dependent amount of basal insulin (20-40%) and affect circadian distribution of insulin needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
14
0
3
Order By: Relevance
“…Our study adds to other reports that showed that various aspects of insulin pump therapy and pump settings have significant effect on metabolic control such as timing of bolus , number of boluses , use of different type of bolus and carbohydrate counting by bolus‐calculator . In addition, different studies have studied the optimal basal insulin rates in children and our findings support the tendency in clinical practice to aim for lowest age dependent basal dose settings for children on CSII in order to optimize glycaemic control and to decrease risks of micro‐vascular complications , .…”
Section: Discussionsupporting
confidence: 80%
“…Our study adds to other reports that showed that various aspects of insulin pump therapy and pump settings have significant effect on metabolic control such as timing of bolus , number of boluses , use of different type of bolus and carbohydrate counting by bolus‐calculator . In addition, different studies have studied the optimal basal insulin rates in children and our findings support the tendency in clinical practice to aim for lowest age dependent basal dose settings for children on CSII in order to optimize glycaemic control and to decrease risks of micro‐vascular complications , .…”
Section: Discussionsupporting
confidence: 80%
“…Since 2003, a new procedure of using D‐W/S‐W boluses has been implemented in the Department of Paediatrics of the Medical University of Warsaw. This procedure was built based on the three main assumptions: meals containing fat and/or proteins should be covered by insulin (e.g., carbohydrate products), meal absorption depends on the type of nutrition product (e.g., rich on fat meals are absorbed during an extended period of time) and insulin dose should be programmed separately for carbohydrate products in N bolus and for fat or/and protein ingredients in the S‐W bolus (11, 12). A new, fat–protein exchange factor was added to the food counting system – defined as 100 kcal of fat and/or protein foods.…”
Section: Methodsmentioning
confidence: 99%
“…It is based on counting protein-fat exchanges (PFE), where 1 PFE is equivalent to 100 kcal coming from proteins and fats. It was assumed that the amount of insulin per 1 PFE is equal to the amount of insulin administered per 1 CE, but the above dosage decays with time in proportion to the amount of consumed PFE [45,46]. It has been shown that the use of this method in a group of pediatric patients is associated with the improvement of glycemic control after a meal rich in protein and fat (pizza) [47].…”
Section: Protein and Fat Exchangesmentioning
confidence: 99%